2022
DOI: 10.1111/1468-4446.12930
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of local inequality: Meritocratic beliefs in unequal localities

Abstract: A puzzle has emerged amidst rising inequality: why do people profess high levels of belief in meritocracy even as income gains are increasingly concentrated at the top?In light of contradictory theories and evidence, we un-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…We found that the effect of perceived economic inequality on meritocratic belief is significant in all models, while the effect of Gini coefficient fell short of statistical significance. These results, to some extent, align with the finding of Morris et al (2022) that economic inequality at local level shows no meaningful association with meritocratic belief in England. Besides, prior studies showed that the negative relation between inequality and subjective well-being disappeared when several previously neglected variables (e.g., GDP per capita) were controlled for (Kelley & Evans, 2017).…”
Section: Theoretical and Practical Implicationssupporting
confidence: 84%
See 2 more Smart Citations
“…We found that the effect of perceived economic inequality on meritocratic belief is significant in all models, while the effect of Gini coefficient fell short of statistical significance. These results, to some extent, align with the finding of Morris et al (2022) that economic inequality at local level shows no meaningful association with meritocratic belief in England. Besides, prior studies showed that the negative relation between inequality and subjective well-being disappeared when several previously neglected variables (e.g., GDP per capita) were controlled for (Kelley & Evans, 2017).…”
Section: Theoretical and Practical Implicationssupporting
confidence: 84%
“…Newman et al (2015) revealed that economic inequality is positively associated with White Americans' rejection of meritocracy, but not associated with non-White Americans' beliefs about meritocracy. The latest evidence showcased that there is no robust relationship between local income inequality and meritocratic beliefs in England (Morris et al, 2022). By contrast, other work that focused on subjective perception of economic inequality has revealed a consistent negative association between inequality perception and belief in meritocracy.…”
Section: Economic Inequality and Belief In Meritocracymentioning
confidence: 98%
See 1 more Smart Citation
“…In this article inequality has been addressed at the level of countries. Some researchers (e.g., Morris et al., 2022; Newman et al., 2015; Solt et al., 2016) have explored meritocracy and inequality as manifested at the local/regional level, aligning with the idea that people's knowledge about inequality might be formed primarily via direct experience. At present, that research is cross‐sectional.…”
Section: Discussionmentioning
confidence: 99%
“…But meritocracy is also sometimes embraced by lower earners, in ways that appear to justify inequality (Ledgerwood et al., 2011; McCoy & Major, 2007; Wiley et al., 2012). Meritocracy becomes a form of ‘resilience’ for lower earners, offering a promise of future advancement (Morris et al., 2022); it thus plays a ‘palliative’ function for people whose subjective well‐being might otherwise suffer in the context of greater deprivation (Hadarics et al., 2021). The prevalence of meritocracy beliefs among lower earners is understood also with reference to ‘relative power theory’: as inequality rises, people at the top have more resources at their disposal, and these resources can support efforts (e.g., using various forms of media) to propagate ‘useful’ ideas among poorer people who might otherwise be inclined to resist their deprived position (Solt et al., 2016).…”
Section: Previous Researchmentioning
confidence: 99%